Salicylic acid enhanced photosynthesis, secondary metabolites, antioxidant and lipoxygenase inhibitory activity (LOX) in Centella asiatica - Ibrahim, Mohd Hafiz; Omar, Hishamuddin; Mohd Zain, Nurul Amalina (Sciencedomain International, 2017)
Aims: The primary aim of this work was to investigate the impact of foliar application of SA on the leaf gas exchange, the accumulation of secondary metabolites and Lipoxygenase Inhibitory activity (LOX) in medicinal plant C. asiatica. Study Design: The study used randomized complete block design (RCBD) replicated three rwith three replications Place and Duration of Study: Department of Biology, Universiti Putra Malaysia between January 2014 and March 2014. Methodology: Cantella asiatica was propagated in individual poly bags filled with sand, coco dust and compost in the ratio of 1:1:1 and chicken dung (50 g) per poly bag. The plant was left for a month in a nursery to be acclimatized until they were ready for SA treatment. After a month, the plants were sprayed with two concentrations (1 µM and 10 µM) of salicylic acid solution (SA). Control plants (0 µM) were sprayed with same solution but without SA. The leaf gas exchange, total flavonoid, saponin, Glutathione (GSH), Oxidized Glutathione (GSSG), Phenyll alanine lyase (PAL), Chalcone synthase activity (CHS) and Lipoxygenase inhibitory activity (LOX) was measured. Results: It was found that production of secondary metabolites (total flavonoids and saponin), GSH, GSSG, PAL, CHS and LOX were solely contributed by interaction of SA levels and plant parts in the descending manner came in leaf treated with 10 µM SA> leaf-1 µM SA>leaf 0 µM SA> stem 10 µM SA> stem 1 µM SA> stem -0 µM SA> root 10 µM SA> root-1 µM SA > root 0 µM SA. High concentration of salicylic acid application (10 µM) was found to be more effective in enhancing the leaf gas exchange traits compared to low concentration (1 µM). Interestingly, it was found that increase in net photosynthesis have a high significant correlation with total flavonoid, total saponin, GSH, GSSG and LOX, indicating that up-regulation of photosynthetic capacity of C. asiatica treated with SA, enhanced the production of secondary metabolites, antioxidant and Lipoxygenase inhibitory activity (LOX). This study also showed that there was involvement of CHS and PAL activity in an increase in the production of secondary metabolites and antioxidant activities under SA application. Conclusion: It was found that SA enhances photosynthetic capacity of C. asiatica. This might be due to increase in PAL and CHS activity that was observed during the study. Furthermore, the production of secondary metabolites, antioxidant enzyme and Lipoxygenase inhibitory activity was elevated during the foliar SA application.